Comparison of Integrated Optical Phase Shifters Designed in Different Regime - Chen Hao; Meng Haoran; Liu Xinyue; Ding Junke; Jiang Jianguang; Chen Gang; Hao Yinlei (MATEC Web of Conferences, 2018)
A comparative study, in aspects of both wavelength dependence and fabrication tolerance, is carried out between silica-based phase shifters designed in two different regime, namely length difference regime and refractive index difference regime. Results show that in the wavelength range of 1500-1600 nm, phase shifter designed in refractive index difference regime has a working wavelength range 2.8~3.1 times wide as that designed in length difference regime; while in the aspect of fabrication tolerance, phase designed in length difference regime is advantageous, with respect to waveguide core dimension error, and waveguide core refractive index error as well.